Endogenous neosynthesis vs. cross-presentation of viral antigens for cytotoxic T cell priming - Freigang, Stefan (National Academy of Sciences, 2003)
Induction of antiviral cytotoxic T lymphocytes (CTLs) has been proposed to require cross-presentation of viral antigens derived from infected extralymphatic host cells by antigen-presenting cells (APC). This postulated mechanism of cross-priming is thought to be essential for CTL responses against viruses that do not infect professional APC, e.g., because of absence of the specific virus receptor. Here, we show for the human pathogen poliovirus that naturally nonpermissive murine APC acquire viral RNA in vivo independently of the cellular virus receptor. Uptake of poliovirus or polioviral RNA initiated neosynthesis of viral antigen to an extent sufficient to prime CTLs in vivo, which were detectable 2-3 wk after infection. Our results do not only indicate that experiments studying cross-presentation and cross-priming by using potentially amplifiable or translatable materials need careful examination, but they also question the general biological importance of cross-presentation and cross-priming in antiviral CTL responses.